Self-Assembly and Hydrogelation of Peptide Amphiphiles - Irwansyah, Irwansyah; Sihombing, Riwandi; Suwarso, Wahyudi Wahyudi (Makara Journal of Science, 2012)
Seven peptide amphiphiles were successfully synthesized using solid phase peptide synthesis method. Peptide amphiphiles were characterized using Matrix-assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometer (MALDI-TOF MS). Atomic force microscopy (AFM) study showed that peptide amphiphiles having glycine, valine, or proline as linker, self-assembled into 100-200 nm nanofibers structure. According to our research, both peptide amphiphile with positive and negative charges bear similar self-assembly properties. Peptide amphiphile also showed its capability as low molecular weight gelator (LMWG). Peptide amphiphiles bearing C-16 and C-12 as alkyl showed better hydrogelation properties than C-8 alkyl. Five out of seven peptide amphiphiles have minimum gelation concentration (MGC) lower than 1% (w/v).